Millennials in the library: promotion of recreational Reading in the digital environment - Echandi Ruiz, Mª. del Pilar (Cuadernos de Documentación Multimedia, 2018)
Academic Reading is an essential activity in the life of every university student. Libraries today can influence the training of critical readers through the use of social web tools and bring young millennials to an attractive and meaningful reading. This study details relevant international experiences of critical and recreational reading implemented in several university libraries and New Resource Centers for Learning and Research (CRAI).